FAKTOR-FAKTOR YANG MEMPENGARUHI KONSUMSI AIR BERSIH DI PDAM TIRTAULI KOTA PEMATANGSIANTAR - Bagudek Tumanggor; Darwin Damanik (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
This study aims to analyze the factors that influence water consumption in PDAM Tirtauli Pematangsiantar City. This research is a quantitative research that examined questionnaire data from household customers from PDAM Tirtauli Pematangsiantar City, namely 30 respondents. The variables of this study consisted of three independent variables, namely the price of water (X1), the number of family members (X2) and the income of family members (X3), and one dependent variable, namely water consumption (Y). This study is a quantitative study analyzed using Multiple Linear Regression with the help of the Eviews 9 program to test and prove the hypothesis. The results of this study are the price of water tariffs (X1), number of family members (X2), and income (X3) have a positive effect on water consumption in PDAM Tirtauli Pematangsiantar City. The coefficient of determination (R2) for the variable price of water tariff, number of family members, and income can explain the variation in the consumption variable of 0.724 or 72.4%. While the remaining 27.6% can be explained by other variables outside the variables of this study.